ANALISIS FAKTOR – FAKTOR YANG MEMPENGARUHI PRODUKTIVITAS TENAGA KERJA WANITA PADA INDUSTRI KAIN TENUN SONGKET MELAYU DI PROVINSI RIAU - Lailatul Fitri; Tri Sukirno Putro; Any Widayatsari (Program Studi Pendidikan Ekonomi Universitas Riau, 2020)
This research was conducted in Riau Province. This study aims to examine the effectof age, lenght of work, wages and the number of dependents on the productivity offemale laborers in the Malay Songket woven textile industry in RiauProvince. Productivity is a description of the ability of workers to produceoutput. The higher the output produced by a worker, shows the higher the level ofproductivity of these workers. This study uses primary data with 100 respondentsworking in the Malay Songket woven textile industry in Riau Province. Withindependent variables, specifically age, lenght of work, wages, and number ofdependents. The analysis technique used is multiple linear regression from crosssectionaldata. Based on the results of research conducted, age, lenght of work,wages, and the number of dependents together have a significant effect on theproductivity of female workers in the Songket Malay woven textile industry in RiauProvince. And partially the lenght of work and wages have a significant influence onthe productivity of women workers in the Malay Songket woven textile industry inRiau Province. This shows that in increasing the productivity of women workers inthe Malay Songket woven textile industry in Riau Province, the factors need to beimproved.